A sequential mediation model for the effect of food safety consciousness on the intention to purchase organic food - Pan, JiaLiang; Wu, Kun-Shan (Frontiers in Sustainable Food Systems, 2024)
This research aims to clarify consumer purchase intentions (PIs) for organic food (OF) in China by investigating factors, including consumers’ food safety consciousness (FSC), health consciousness (HC), and attitude (AT) toward OF. To collect data for this study, online surveys were carried out sequentially among 350 respondents, and partial least squares structural equation modeling (PLS-SEM) was employed to test the proposed hypotheses regarding the direct and indirect effect of FSC on PI and the sequential mediating effect of HC and AT. The findings indicate that consumers’ FSC strongly influences their intention to purchase OF and is sequentially mediated by HC and AT. PI is also significantly impacted by HC and is mediated by AT, and AT directly significantly influences PI. Through multiple group analyses, the path from HC to AT is found to be moderated by education. Accordingly, suggestions for OF businesses and future research are provided to improve public health.